Financial literacy and intra-household decision making: Evidence from Rwanda - Antonia Grohmann; Annekathrin Schoofs (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Despite considerable policy efforts, women continue to be underrepresented in positions of power and decision making. As an important aspect of women empowerment, we examine women's participation in intrahousehold financial decision making and how this is affected by financial literacy. Using both OLS and IV regression analysis, we show that women with higher financial literacy are more involved in household financial decisions. In line with the literature, we further find that women are less financially literate than men. Results from decomposition analysis show that education and personality traits (openness, happiness, and depression) drive this financial literacy gender gap.
Keywords: D14; J16; G02; 330; financial literacy; women empowerment; intra-household decision making